There is no rose : the Mariology of the Catholic Church - Nichols, Aidan (Fortress Press, 2015)
This study contributes to the revival of a more full-blooded Marian teaching and attempts to take the path set by ressourcement theology in recovering the robust voice of witness to Mary. Aidan Nichols, OP, works through the biblical, patristic, and medieval sources and introduces readers to the robust scriptural and theological bases for the Church's celebration of Mary. He argues for the crucial relevance of Mary in the theological articulation of the gospel, the celebration and practice of the liturgy, and the sacramental life of the Church.